Improvement of Pancasila Education Learning Activities Through the Project Based Learning (PjBL) Model for Third Grade Elementary School: Peningkatan Aktivitas Belajar Pendidikan Pancasila Melalui Model Project Based Learning (PjBL) Siswa Kelas III Sekolah Dasar - Priya Kusuma Bahari; Abdulkadir Rahardjanto; Oktaviani Adhi Suciptaningsih; Siti Mas’ula; Fina Liswati Rahayu; Tri Susilowati (Universitas Sriwijaya in Collaboration with HDPGSDI (Himpunan Dosen PGSD Indonesia), 2025)
This research aims to determine the implementation of the Project Based Learning (PjBL) model to enhance the learning activities of third-grade students at SD Negeri Tlogomas 2, Malang City, in the subject of Pancasila Education. Using the Classroom Action Research (CAR) approach, this study was conducted in two cycles involving planning, implementation, observation, and reflection. The project of creating a Pop Up Book became the main focus, where students collaborated to illustrate the values of Pancasila in the context of our ethnic group's wealth. The research results show a significant increase in student learning activities, from 46,91% in the first cycle to 86,52% in the second cycle. These findings indicate that the PjBL model not only enhances student engagement but also deepens their understanding of Pancasila concepts. This research provides new insights for educators regarding more interactive and engaging teaching methods, and emphasizes the importance of relevant learning experiences to enhance student motivation and participation in the learning process.